Solid‐State Phosphorescence of A2[W6I14] with A = PPN, PPh4. Issue 37 (26th September 2019) - Hummel, Thorsten; Ströbele, Markus; Fuhrmann, Arin‐Daniel; Enseling, David; Jüstel, Thomas; Meyer, Hans‐Jürgen
Abstract : Hybrid organic‐inorganic cluster compounds A 2 [W6 I14 ] with A = Ph4 P, PPN were prepared by cation exchange reactions from Cs2 [W6 I14 ] with a corresponding organic halide; and a purification method for A 2 [W6 I14 ] compounds by column chromatography is introduced. Crystal structures of compounds were solved and refined based on single‐crystal X‐ray diffraction data. Photoluminescence properties of the new A 2 [W6 I14 ] compounds reveal orange to deep‐red emission on excitation between 300 and 500 nm. (PPN)2 [W6 I14 ] is an exception among compounds with the [W6 I14 ] 2– ion, showing a solid‐state phosphorescence with a quantum yield (ϕP ) in the order of 40 %. Abstract : Hybrid organic‐inorganic cluster compounds A 2 [W6 I14 ] with A = Ph4 P, PPN are presented, and a purification method is introduced. Photoluminescence studies reveal a remarkable phosphorescence for (PPN)2 [W6 I14 ].